PROXIMATE COMPOSITION OF SELECTED HERMETICALLY STORED COWPEA (Vigna unguiculata) - Oyefeso, Babatunde Olayinka; Muili, Toheeb Olayode; Omobowale, Mobolaji O.; Fadele, Oluwaseyi K. (FUDMA JOURNAL OF SCIENCES, 2025)
Cowpea (Vigna unguiculata) is a food grain legume which serves as an important source of protein for many people in Nigeria and other developing nations. Cowpea storage helps to maintain all- year round supply, stabilize market price and minimize postharvest losses. This study investigated the effect of storage period on the proximate composition of two varieties (viz. brown and black-eyed cowpea) of cowpea seeds stored hermetically in plastic bins in a humid tropical environment. The cylindrical plastic bins used for storage were of dimensions 0.75 m height and 0.35 m diameter and they were filled up to 0.70 m height (capacity of 0.0674 m3). Proximate analysis was carried out on the samples before and after a storage period of 90 days. The outcome of study showed the colour of the two varieties of the cowpeas to remain the same after a period of 90 days storage. Also, no living insects were found after storage and which makes the hermetic storage of cowpea grains with polythene bag in plastic bin to be effective. The moisture content, protein, crude fibre, ash content, ether extract and dry matter of the brown-eyed cowpea before storage were established to be 5.91%, 24.15%, 3.3%, 3.1% and 4.5%; while that the black-eyed cowpea were 6.45%, 20.05%, 3.1%, 2.9% and 3.9% respectively. The proximate composition of the two varieties tend to increase after storage; the brown-eyed cowpea was found to have moisture content, protein, crude fibre, ash content, ether extract and dry matter of 12.85, 27.65, 7.8, 2.9...